2007
DOI: 10.1026/1617-6391.6.2.60
|View full text |Cite
|
Sign up to set email alerts
|

Die Nutzung psychologischer Verfahren der externen Personalauswahl in deutschen Unternehmen

Abstract: Zusammenfassung. Die vorliegende Untersuchung bietet eine aktuelle Aufstellung der Einsatzhäufigkeiten verschiedener Personalauswahlverfahren. Mit Angaben von 125 deutschen Unternehmen unterschiedlicher Größe und Branche stellt diese Erhebung eine Fortsetzung der Studien aus den beiden vergangenen Jahrzehnten dar ( Schulz, Schuler & Stehle, 1985 ; Schuler, Frier & Kauffmann, 1993 ). Das Einstellungsinterview und die Analyse von Bewerbungsunterlagen bestätigen sich als verbreitetste Auswahlverfahren, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(27 citation statements)
references
References 3 publications
1
18
0
8
Order By: Relevance
“…Our results are in line with previous findings showing that German companies rarely use psychometric tests in comparison with other countries (Ryan et al, 1999), which may be based on ideologically rooted reservations (Krause & Gebert, 2003). The infrequent use of trait-oriented methods can also be traced back to low acceptance among both companies (König, Klehe, Berchtold, & Kleinmann, 2010;Schuler, Hell, Trapmann, Schaar, & Boramir, 2007) and applicants (Anderson, Salgado, & Hülsheger, 2010). Albeit speculatively, reasons for the low acceptance of intelligence tests could be the frequently abstract task designs and the minor face validity (Chan, Schmitt, DeShon, Clause, & Delbridge, 1997).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results are in line with previous findings showing that German companies rarely use psychometric tests in comparison with other countries (Ryan et al, 1999), which may be based on ideologically rooted reservations (Krause & Gebert, 2003). The infrequent use of trait-oriented methods can also be traced back to low acceptance among both companies (König, Klehe, Berchtold, & Kleinmann, 2010;Schuler, Hell, Trapmann, Schaar, & Boramir, 2007) and applicants (Anderson, Salgado, & Hülsheger, 2010). Albeit speculatively, reasons for the low acceptance of intelligence tests could be the frequently abstract task designs and the minor face validity (Chan, Schmitt, DeShon, Clause, & Delbridge, 1997).…”
Section: Discussionsupporting
confidence: 90%
“…Second, we focused on the internal selection of candidates for the AC. Given the differences between internal and external recruiting processes (Bartram, 2004;Becker et al, 2011;Schuler et al, 2007), it would be interesting to extend our research to preselection methods that are used for the external nomination of AC candidates. Third, because we surveyed only German companies, research is necessary to generalize our results to other countries.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to test our causal hypotheses, we needed an experimental design, and convincing test publishers to manipulate their promotion material was deemed impossible. Furthermore, personality tests are not used that often (e.g., Diekmann & König, in press;Schuler et al, 2007), making the decision for or against a test a rare event. Therefore, the disadvantage of the use of a hypothetical scenario must be considered together with the advantage of being able to draw causal conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…One prominent example is the pronounced preference for the unstructured interview (Lievens & De Paepe, 2004;Stephan & Westhoff, 2002), even though research has shown that standardization leads to higher validity (Kepes, Banks, McDaniel, & Whetzel, 2012;McDaniel, Whetzel, Schmidt, & Maurer, 1994). The role of general mental ability in personnel selection, as another example, has been emphasized for decades now (Schmidt & Hunter, 1998), but tests of cognitive ability are used only occasionally (e.g., companies surveyed by Ryan, McFarland, Baron, & Page, 1999, indicated the extend of use of cognitive ability tests with 21-50%, and only 30% of German companies use cognitive ability tests with at least some applicants; Schuler, Hell, Trapmann, Schaar, & Boramir, 2007). On the other hand, even methods like graphology, which have been found to be inappropriate in selection procedures (Driver, Buckley, & Frink, 1996), still find some supporters (Berchtold, 2005;Di Milia, Smith, & Brown, 1994;Ryan et al, 1999;Shackleton & Newell, 1994), although this is not as widespread as is sometimes believed (Bangerter, König, Blatti, & Salvisberg, 2009).…”
Section: Introductionmentioning
confidence: 99%